Strategy for the Development of the Indonesian Halal Industry in the New Normal Era - Gunawan Aji; Ummu Najwa; Ummu Najwa Akyani; Armaelis Arfani; Elsa Tiara (Basic and Applied Accounting Research Journal, 2023)
The COVID-19 pandemic has had a significant impact on consumer buying patterns. This makes the economic sector receive special attention from the Indonesian government. At present the Indonesian government has implemented a new normal policy to accelerate the handling of COVID-19. This study aims to explain the role of the halal industry in reviving the Indonesian economy in the new normal era, the opportunities for the halal industry in Indonesia, and the possible challenges it faces, and explain what strategies should be followed. This study uses a descriptive qualitative research method. The technique used in this study using a purposive sampling technique. The data used comes from primary data through interviews and secondary data through research, books, other articles, and the official website of the Minister of Finance relevant to the research theme. The results of this study explain that the halal industry has an important role in Indonesia's economic growth in the new normal era. There are economic sectors that are opportunities for the development of the halal industry, namely halal food and beverages, halal fashion, halal cosmetics, halal media and recreation, halal pharmaceuticals, and halal finance. Apart from opportunities, a number of challenges must be faced, such as challenges arising from government, organizations, development, society or consumers, and existing resources. Strategies also need to be carried out to deal with these challenges, one of which is by prioritizing the halal product category.